Schizophrenia - Marder, Stephen R., 1945- (Oxford American psychiatry library., 2014)
This text provides a person-centered approach to helping individuals with schizophrenia meet their personal goals.The approach is strongly influenced by the ""recovery"" model. This model emphasizes a respect for an individual's ability to participate in decision-making about their illness and an appreciation that people can achieve many of their personal goals even when their illness is only partially controlled. There is also an emphasis on the diversity of individuals with schizophrenia.That is, although many people with this illness are severely disabled with limitations in their abilities.